2020
DOI: 10.4047/jap.2020.12.5.299
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the accuracy of six intraoral scanners on prepared teeth and effect of scanning sequence

Abstract: PURPOSE The aim of this study was to evaluate the accuracy of six recently introduced intraoral scanners (IOSs) for single crown preparations isolated from the complete arch, and to determine the effect of scanning sequence on accuracy. MATERIALS AND METHODS A complete arch with right and left canine preparations for single crowns was used as a study model. The reference dataset was obtained by scanning the complete arch using a highly accurate industrial scanner (ATOS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 30 publications
(76 reference statements)
3
30
0
Order By: Relevance
“…The trueness and precision of intraoral scanners has been investigated in numerous scenarios by different authors. The results of this study were consistent with the results of other previous studies [22][23][24]. Mutwalli et al evaluated the accuracy of three IOS (Trios 3, Trios 3 mono, Itero element) and obtained significant differences between the digital impressions [22].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The trueness and precision of intraoral scanners has been investigated in numerous scenarios by different authors. The results of this study were consistent with the results of other previous studies [22][23][24]. Mutwalli et al evaluated the accuracy of three IOS (Trios 3, Trios 3 mono, Itero element) and obtained significant differences between the digital impressions [22].…”
Section: Discussionsupporting
confidence: 91%
“…Diker and Tak evaluated the accuracy of six IOS in the scenario of multiple single crown preparations distributed across a dentate arch. They reported the highest accuracy (trueness, precision) for Primescan (25 and 10 µm), followed by Trios (40.5 and 11 µm), Omnicam (41.5 and 18 µm), Virtuo Vivo (52 and 37 µm), iTero (70 and 12 µm) and Emerald (73.5 and 60 µm) [23]. Ender et al also evaluated the trueness and precision of eight IOS and concluded that there were significant differences between the digital impressions, the best values being obtained for the Primescan IOS [24].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study (Diker & Tak, 2020) evaluated six different intraoral scanning systems and found that there was no statistical significant difference between TRIOS and iTero, the same scanners evaluated in the present study. However, different from the present study, the authors performed 3D models superimpositions to obtain trueness and precision values.…”
Section: Discussionsupporting
confidence: 45%
“…4,25 Many scan strategies for complete arches have been recommended. [21][22][23][24][25][26][27] Oh et al 26 analyzed the 3D accuracy by using 3 scan strategies with 2 IOSs (i500 and TRIOS3); in the present study, 3D analysis was performed by applying the scan strategy that showed the best accuracy (Fig. 2A).…”
Section: Discussionmentioning
confidence: 76%
“…In previous studies, because the IOS could scan only 1 or 2 teeth at a time in one direction in the oral cavity, many scan strategies for complete-arch scanning have been proposed to improve accuracy. [21][22][23][24][25][26][27] However, the optimum scan strategy for the most accurate scan has not yet been established. The recommended scan range of an IOS for fixed dental prostheses has been reported in the first part of the present study.…”
mentioning
confidence: 99%